Investigating Factors Affecting the Use of Spoken and Written English in School (International Journal Online of Humanities, 2020)
This paper is from a research work and it investigated factors affecting the effective use of oral and written English in senior secondary schools.  The study revealed that some teachers who teach oral English are not committed teachers even though they have the requisite qualifications in English Language.  The study further revealed that a large percentage of teachers of English Language teach the subject only few weeks before WASSCE using the wrong methodology.  Also, the appropriate materials such as textbooks are not easily available or accessible: workshops and tutorials are not usually conducted for teachers; teachers are not motivated and thus pupils lack interest in the subject.